In vivo MR imaging of intravascularly injected magnetically labeled mesenchymal stem cells in rat kidney and liver - Bos, Clemens; Delmas, Yahsou; Desmoulière, Alexis; Solanilla, Anne; Hauger, Olivier; Grosset, Christophe; Dubus, Isabelle; Ivanovic, Zoran; Rosenbaum, Jean; Charbord, Pierre; Combe, Christian; Bulte, Jeff W M; et al. (Radiology, 2004)
To evaluate in vivo magnetic resonance (MR) imaging with a conventional 1.5-T system for depiction and tracking of intravascularly injected superparamagnetic iron oxide (SPIO)-labeled mesenchymal stem cells (MSCs). This study was conducted in accordance with French law governing animal research and met guidelines for animal care and use. Rat MSCs were labeled with SPIO and transfection agent. Relaxation rates at 1.5 T, cell viability, proliferation, differentiation capacity, and labeling stability were assessed in vitro as a function of SPIO concentration. MSCs were injected into renal arteries of healthy rats (labeled cells in four, unlabeled cells in two) and portal veins of rats treated with carbon tetrachloride to induce centrolobular liver necrosis (labeled cells and unlabeled cells in two each). Follow-up serial T2*-weighted gradient-echo MR imaging and R2* mapping were performed. MR imaging findings were compared histologically. SPIO labeling caused a strong R2* effect that increased linearly with iron dose; R2* increase for cells labeled for 48 hours with 50 microg of iron per milliliter was 50 sec(-1) per million cells per milliliter. R2* was proportional to iron load of cells. SPIO labeling did not affect cell viability (P > .27). Labeled cells were able to differentiate into adipocytes and osteocytes. Proliferation was substantially limited for MSCs labeled with 100 microg Fe/mL or greater. Label half-life was longer than 11 days. In normal kidneys, labeled MSCs caused signal intensity loss in renal cortex. After labeled MSC injection, diseased liver had diffuse granular appearance. Cells were detected for up to 7 days in kidney and 12 days in liver. Signal intensity loss and fading over time were confirmed with serial R2* mapping. At histologic analysis, signal intensity loss correlated with iron-loaded cells, primarily in renal glomeruli and hepatic sinusoids; immunohistochemical analysis results confirmed these cells were MSCs. MR imaging can aid in monitoring of intravascularly administered SPIO-labeled MSCs in vivo in kidney and liver.